Kebermanfaatan Feri Penyeberangan dalam Menunjang Aktivitas Sosial Ekonomi Masyarakat: Studi kasus di Desa Ayawan, Kecamatan Seruyan Tengah, Kabupaten Seruyan, Kalimantan Tengah - Ripqi Aditia Saputra; Jelita Jelita; Sofyan Hakim; Muhammad Noor Sayuti (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Ferry crossings constitute a vital transportation infrastructure for rural communities separated by river systems and lacking bridge connectivity. In Ayawan Village, Central Seruyan District, Seruyan Regency, community mobility, access to public services, and economic activities are highly dependent on ferry transportation. Despite its strategic role, studies examining the direct socio-economic benefits of ferry crossings in isolated rural areas remain limited. Employing a descriptive qualitative field approach, data were gathered through observation, semi-structured interviews, and documentation involving ferry users, ferry operators, community leaders, and village officials. Data validity was ensured through source triangulation and analyzed using the Miles and Huberman interactive model. The findings indicate that ferry crossings contribute significantly to two interconnected dimensions. Socially, they facilitate access to education, healthcare services, public administration, and interregional social interaction. Economically, they support the distribution of agricultural and plantation products, trading activities, labor mobility, and broader market accessibility. The analysis further demonstrates that ferry services function not only as transportation infrastructure but also as an essential instrument for sustaining community welfare. From the perspective of maslahah, ferry crossings fulfill hajiyah needs by providing social and economic convenience and, in certain circumstances, approach the level of dharuriyah due to their importance for maintaining access to education, health services, and livelihoods. These findings highlight the necessity of strengthening ferry services as part of equitable and sustainable rural transportation development policies.